2020
DOI: 10.3390/s20154261
|View full text |Cite
|
Sign up to set email alerts
|

Precipitable Water Vapor Retrieval from Shipborne GNSS Observations on the Korean Research Vessel ISABU

Abstract: We estimate precipitable water vapor (PWV) from data collected by the low-cost Global Navigation Satellite System (GNSS) receiver at a vessel. The dual-frequency GNSS receiver that the vessel ISABU is equipped with that is operated by the Korea Institute of Ocean Science and Technology. The ISABU served in the Pacific Ocean for scientific research during a period from August 30 to September 21, 2018. It also performs radiosonde observations to obtain a vertical profile of troposphere on the vessel’s path. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
(49 reference statements)
0
1
1
Order By: Relevance
“…Comparisons with radiosondes exhibit a large difference in rms (4.29 kg m −2 and 3.59 kg m −2 for REUN and KERG, respectively) and bias (2.54 kg m −2 and 2.36 kg m −2 for REUN and KERG, respectively), with radiosonde wetter than ship-borne GNSS. These differences are larger than those presented in the majority of previous studies [33,49], even if larger ones are also observed [54]. We have previously mentioned that such radiosondes (Modem M10) were mainly known to have dry bias, which is not the case here.…”
Section: Assessment Of Gnss Iwv Retrievalcontrasting
confidence: 76%
“…Comparisons with radiosondes exhibit a large difference in rms (4.29 kg m −2 and 3.59 kg m −2 for REUN and KERG, respectively) and bias (2.54 kg m −2 and 2.36 kg m −2 for REUN and KERG, respectively), with radiosonde wetter than ship-borne GNSS. These differences are larger than those presented in the majority of previous studies [33,49], even if larger ones are also observed [54]. We have previously mentioned that such radiosondes (Modem M10) were mainly known to have dry bias, which is not the case here.…”
Section: Assessment Of Gnss Iwv Retrievalcontrasting
confidence: 76%
“…A validation of the GPS PWV using radiosonde data found the system to be highly accurate, with a mean bias of −0.1 mm and root mean square of 1.7 mm. A method for analysing PWV using a low-cost GNSS receiver installed onboard the ISABU vessel, operated by the Korea Institute of Ocean Science and Technology, was developed by Sohn et al, (2020) [26]. Radiosonde data and GNSS PWV were found to be in close agreement in their validation.…”
Section: Introductionmentioning
confidence: 98%